2017
DOI: 10.3906/zoo-1512-23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum, copper, and titanium nanoparticles onsome blood parameters in Wistar rats

Abstract: IntroductionFollowing recent technological developments, nanosized (<100 nm) metal complexes have entered into different areas of human lives and the discussion of their potential effects on humans and the environment has begun (Jeng and Swanson, 2006;Janrao et al., 2014). The areas in which nanoparticles (NPs) are used for anthropogenic purposes include medicine, the textile and electronic industries, filters, toothpaste, suntan cream, toys, moisturizers, packing products, household appliances, and the food i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…48 Canli et al reported an increase in the total oxidant status in the blood of rats exposed to CuO-NPs. 49 Also, CuO-NPs were used as a chemical model for the induction of oxidative stress in rats to study the effectivity of resveratrol in the protection against oxidative damages in liver and kidney. 6 In the present study, the decrease in cell viability observed could be due to an increase in oxidative stress after exposure to CuO-NPs (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…48 Canli et al reported an increase in the total oxidant status in the blood of rats exposed to CuO-NPs. 49 Also, CuO-NPs were used as a chemical model for the induction of oxidative stress in rats to study the effectivity of resveratrol in the protection against oxidative damages in liver and kidney. 6 In the present study, the decrease in cell viability observed could be due to an increase in oxidative stress after exposure to CuO-NPs (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…ZnO nanoparticles have caused cellular shrinkage and significantly decreased mitochondrial functionality at doses between 50 and 100 µg/mL, in a concentration, size and time dependent manner [ 136 , 143 ]. CuO and Al 2 O 3 nanoparticle exposure has been found to cause oxidative stress, with TiO 2 nanoparticles causing liver damage in rats [ 144 ].…”
Section: Stability and Toxicity Of Micro And Nanomaterialsmentioning
confidence: 99%
“…Liver enzymes and kidney functions (ALT, AST, Bil, urea, and creatinine) in serum were considered as important serum parameters for investigating animal health [46]. Biochemical analysis of liver and kidney function parameters of AlCl -hepatorenal injured mice treated with ZnO NPs and followed by zinc ions redistribution from the liver to other organs.…”
Section: Data Availability Concerning the Accumulation Of Zno Nps In mentioning
confidence: 99%